2003
DOI: 10.1093/hmg/ddg274
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and subcellular localization of the ARPKD protein; fibrocystin is expressed on primary cilia

Abstract: Autosomal recessive polycystic kidney disease (ARPKD) is an infantile form of PKD characterized by fusiform dilation of collecting ducts and congenital hepatic fibrosis. The ARPKD gene, PKHD1, is large (approximately 470 kb; 67 exons) with a 12222 bp longest open reading frame, although multiple different splice forms may be generated. The predicted full-length ARPKD protein, fibrocystin, is membrane bound with 4074 amino acids (447 kDa molecular weight). To characterize the pattern of fibrocystin expression w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
210
0
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(217 citation statements)
references
References 34 publications
2
210
0
5
Order By: Relevance
“…FPC was demonstrated to localize to the primary cilium and/or basal bodies of renal tubular epithelia, [27][28][29][30][31] and malformation of the cilia was shown to induce cyst formation in the kidneys 34,35 ; therefore, we began to determine whether the lack of FPC also disrupts ciliogenesis in Pkhd1-deficient mice. We used IF with an anti-acetylated ␣-tubulin antibody to examine the number and morphology of renal primary cilia in 6-moold littermates.…”
Section: Lack Of Fpc Exhibits Aberrant Ciliogenesis In the Renal Epitmentioning
confidence: 99%
See 1 more Smart Citation
“…FPC was demonstrated to localize to the primary cilium and/or basal bodies of renal tubular epithelia, [27][28][29][30][31] and malformation of the cilia was shown to induce cyst formation in the kidneys 34,35 ; therefore, we began to determine whether the lack of FPC also disrupts ciliogenesis in Pkhd1-deficient mice. We used IF with an anti-acetylated ␣-tubulin antibody to examine the number and morphology of renal primary cilia in 6-moold littermates.…”
Section: Lack Of Fpc Exhibits Aberrant Ciliogenesis In the Renal Epitmentioning
confidence: 99%
“…The longest open reading frame is predicted to include 66 exons and to encode the 4074 -amino acid membrane-associated receptor-like protein fibrocystin/polyductin (FPC). [23][24][25][26] It was shown that FPC is associated with the basal bodies/primary cilia of epithelial cells [27][28][29][30] and co-localizes with PC2 within the cell. 31 These observations suggest the possibility that FPC and PC2 may function in a common molecular pathway in vivo.…”
mentioning
confidence: 99%
“…When these genes are mutated, the absence of their protein products results in ciliary dysfunction and cyst formation. [6][7][8][9][10][11] Development of cysts in the liver is the most frequent extra-renal manifestation in both ADPKD and ARPKD. 10-13 Although in ADPKD the liver generally functions normally, the progressive increase in size of the polycystic liver causes abdominal pain, early postprandial fullness and/or shortness of breath, and thus significantly affects quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Developing and mature intrahepatic bile ducts express the PKHD1 protein, fibrocystin, whereas bile ducts of ARPKD patients lack its expression. 8 Mice with targeted mutation of Pkhd1 develop cystic biliary dysgenesis and portal fibrosis. 9 In the PCK rat, cholangiocytes possess short and malformed cilia that do not express fibrocystin.…”
mentioning
confidence: 99%